The effectiveness of morphemic analysis instruction towards ESL students' vocabulary development / Chandrakala Veratharajoo - Chandrakala, Veratharajoo (2016)
The aim of the current study was to observe the effect of compounding, inflectional and derivational morphemic awareness on vocabulary development among ESL low proficiency secondary school learners in Malaysia. The study was a quasi-experimental research and data were collected through statistical analysis SPSS version 22, ANCOVA. The findings of the current study can be mentioned in two main discussions. The first, second and third research question results revealed that individual instruction of three types of morphemic analysis awareness had contributed significant results on the participants’ inflectional, derivational and compounding knowledge, at various degrees. Inflectional morpheme instruction had the most significant effect on their morphological awareness, followed by compounding, and the least effective instruction was on derivatives. In the second discussion, fourth, fifth and the sixth research question results revealed that inflectional, derivational and compounding morphemic knowledge contributed different levels of vocabulary development among the participants. The compounding morphemic knowledge was found to have the least effect while inflectional morphemic knowledge had the most significant effect on participants’ vocabulary development. Thus, the results of the current study demonstrate that inflectional morphemic instruction emerged as the most significant factor for morphemic analysis awareness that helped ESL low proficiency secondary school learners to develop their vocabulary effectively. The study implies that ESL learners’ vocabulary development can be improved through morphemic analysis instruction. The study also highlights that a vocabulary lesson should be accompanied by morphemic analysis instructional strategy for better language teaching and learning. Morphemic analysis should be considered as an alternative instruction to facilitate low proficiency learners’ vocabulary development throughout secondary schools in the ESL context.